Pediatric Cervical Spine Injuries - Yadav, Awdhesh; Singh, Aneeta; Verma, Rajat; Singh, Vijay K.; Ojha, Bal K.; Chandra, Anil; Srivastava, Chhitij (Asian Journal of Neurosurgery, 2022)
Objective Pediatric cervical spine injuries are rare and account for 1 to 2% of all pediatric spine injuries. There is a paucity of data on pediatric cervical spine injuries in developing countries like India. The purpose of this study is to review and analyze our 5 years of experience with pediatric cervical spine injuries.Methods All the available medical records over the 5 years were reviewed retrospectively. The data was analyzed to know the epidemiology, mechanism of injury, injury patterns, management, and outcome. The patients were divided into two groups: 0 to 9 years and 10 to 18 years.Results Seventy-five eligible records were included in our study. The incidence of cervical spine injuries was significantly lower in younger children than the older ones (p < 0.042). The most common mechanism of injury was fall from height: 33 (44%) patients followed by road traffic accidents: 27 (36%) patients. The involvement of the upper cervical spine was significantly higher in younger children (p < 0.001). Fractures with subluxation were the most common pattern of injury, observed in 35 (47%) patients. However, fractures with subluxation were uncommon in younger children compared with older children (p < 0.04). Spinal cord injury without radiographic abnormality (SCIWORA) was observed in 42% of younger children compared with 8% of older children (p < 0.02). Thirty (40%) patients were managed surgically; anterior cervical corpectomy with fusion was the most commonly performed procedure in 19 (63%) patients. The overall mortality was 20%.Conclusion The results of our study revealed predominant involvement of the upper cervical spine in children younger than 10 years of age. SCIWORA was documented in both the age groups with a significantly higher incidence in younger children. The instrumentation and fusion techniques in children are safe; however, developing pediatric spine needs special considerations.
Keywords: pediatric; cervical spine injury; SCIWORA